Dampak Pemberian Semangat dan Suasana Kerja Kondusif pada Kinerja Pegawai Dinas Kependudukan/Catatan Sipil Kota Tebing Tinggi - Rumiris Siahaan; Rusmewahni Rusmewahni (Ekonomis: Journal of Economics and Business, 2020)
The purpose of this study was to determine the impact of encouragement and work atmosphere on employee performance at the Tebing Tinggi City Civil Registry. The independent variable of this study consists of encouragement and work atmosphere, while the dependent variable is employee performance. This research is a quantitative descriptive study. The research was conducted on the employees of Tebing Tinggi City Civil Registry. The data used are primary data obtained through questionnaire answers from 27 respondents. Data were analyzed using multiple linear regression analysis method. The results showed that encouragement had a significant impact on employee performance at the Tebing Tinggi City Civil Registry. The work atmosphere was also found to have a significant impact on the employee performance of the Tebing Tinggi City Civil Registry